2022
DOI: 10.1371/journal.pone.0276180
|View full text |Cite
|
Sign up to set email alerts
|

Participatory peer research exploring the experience of learning during Covid-19 for allied health and healthcare science students

Abstract: Introduction The teaching and learning experience of allied health and healthcare science students has altered because of the Covid-19 pandemic. Limited research has explored the experience on the future healthcare workforce using participatory research design. The aim of this study was to explore the impact of a global pandemic on the clinical and academic experiences of healthcare student using a co-production approach with student peer researchers. Methods A participatory research approach adopting online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Data about the effect of COVID-19 on students exists, but far less guidance is available about what is needed to support students in this and future epidemics, especially from a participatory research framework and/or students’ perspectives (Daly Lynn et al, 2022 ). In this study, conversations among or overheard by peer-ethnographers revealed specific and contextual points of concerns where health information and behaviour interventions are needed such as vaccines, off-campus events, conflict resolution, and immunocompromised students.…”
Section: Discussionmentioning
confidence: 99%
“…Data about the effect of COVID-19 on students exists, but far less guidance is available about what is needed to support students in this and future epidemics, especially from a participatory research framework and/or students’ perspectives (Daly Lynn et al, 2022 ). In this study, conversations among or overheard by peer-ethnographers revealed specific and contextual points of concerns where health information and behaviour interventions are needed such as vaccines, off-campus events, conflict resolution, and immunocompromised students.…”
Section: Discussionmentioning
confidence: 99%
“…12 [14] Rapid changes to learning, living alongside COVID-19 and psychological impact, and a gap in confidence in clinical skills development. The study recommended a hybrid approach to delivery and further research on the effects of the pandemic on student learning.…”
Section: [2]mentioning
confidence: 99%